Підхід до створення інтелектуального помічника для наукових конференцій на основі LLM та PFE - Теплюк, М. В.; Гриньова, О. Є. (ХНУРЕ, 2025)
The article describes the development of an intelligent assistant for the website of the International Forum of Young Scientists «Radio Electronics and Youth in the XXI Century» to automate the search for similar scientific papers and answer frequently asked questions. A combination of NLU and PFE is used. The system is based on the SBERT model for fast semantic text comparison, Ukr- RoBERTa-base for Ukrainian language processing, and ChatGPT for checking the structure of papers. This solution will enhance the forum's efficiency and the quality of research.
Keywords: інтелектуальний помічник; LLM; PFE